Nutritive Values of some Lesser Known Herbivore Foods from Melghat Tiger Reserve (maharashtra) - Deshmukh, V. R.; Dhore, M. A. (Indian Forester, 1994)
A study was undertaken to determine nutritive values of eight lesser known plant foods of wild herbivores like Gaur, sambar etc. from Melghat Tiger Reserve. These materials are also the food of domestic cattle from tribal villages located in buffer zone of this Reserve. The main components of proximate analysis of food-stuffs like crude protein, crude fat, crude fibre. Soluble carbohydrates (NFE) and solule carbohydrates (including ash) were estimated by Weende system of proximate analysis. All the forage materials studied namely. Heteropogon ritchiei, Pseudanthistiria hispida, Chloris dolichostachya, Clitoria biflora, Milletia auriculata, Zizyphus xylopyra, Flacourtia indica, Securinega virosa are significant floristic components found in wider area of Melghat Tiger Reserve. The three grass species studieds contain higher % of carbohydrates, whereas plant parts of Securinega virosa used as feed-stuff by herbivores contain high % of crude protein.